Pengembangan Instrumen Literasi dan Numerasi Berbasis TIK Untuk Siswa Sekolah Dasar - Mulyadi; Kunto Imbar Nursetyo (Jurnal Pembelajaran Inovatif, 2022)
This development research aims to produce products in the form of Literacy and Numeration instruments as a complement to learning for fifth grade elementary school students in facing the National Assessment (AN) as a substitute for the National Examination (UN). This development was carried out based on the observations of researchers, namely that there were still many elementary students and teachers who were not ready to face the national assessment. The development of this instrument refers to the product development model, namely the Rapid Prototyping development model. Based on this model, this development research has gone through the stages of needs assessment and content analysis, setting learning objectives, developing prototypes, utilizing prototypes, and installing systems. The evaluation in this study uses formative evaluation involving two experts, namely material experts and learning media experts as well as users, namely students and teachers of SD Class V. Based on the processes and procedures in developing learning products, it can be concluded that this development research entitled Development of Minimum Competency Assessment Instruments for elementary students is very good. Abstrak Penelitian pengembangan ini bertujuan untuk menghasilkan produk berupa instrument Literasi dan Numerasi sebagai pelengkap pembelajaran untuk siswa kelas V SD dalam menghadapi Asesmen Nasional (AN) sebagai pengganti Ujian Nasional (UN). Pengembangan ini dilakukan berdasarkan hasil pengamatan peneliti yaitu masih banyak siswa SD dan guru yang belum siap dalam menghadapi asesmen nasional. Pengembangan instrumen ini mengacu pada model pengembangan produk yaitu model pengembangan Rapid Prototyping. Berdasarkan model tersebut, penelitian pengembangan ini telah melalui tahap analisis penilaian kebutuhan dan analisis konten, menetapkan tujuan pembelajaran, mengembangkan prototipe, memanfaatkan prototipe, dan memasang sistem. Evaluasi pada penelitian ini menggunakan evaluasi formatif dengan melibatkan dua ahli yaitu ahli materi dan ahli media pembelajaran serta pengguna yaitu siswa dan guru SD Kelas V. Berdasarkan proses dan prosedur dalam mengembangkan produk pembelajaran maka dapat disimpulkan bahwa penelitian pengembangan ini yang berjudul pengembangan instrument asesmen kompetensi minimum untuk siswa SD sangat baik.